2021
DOI: 10.14444/8083
|View full text |Cite
|
Sign up to set email alerts
|

Final Long-Term Reporting from a Randomized Controlled IDE Trial for Lumbar Artificial Discs in Single-Level Degenerative Disc Disease: 7-Year Results

Abstract: Background: This study compared 7-year safety and efficacy outcomes of activL and ProDisc-L lumbar total disc replacements in patients with symptomatic, single-level lumbar degenerative disc disease (DDD). The objectives are to report 7-year outcomes of the trial, evaluate the outcomes for patients lost to follow-up, and determine whether early outcomes predict long-term outcomes.Methods: This was a prospective, multicenter, randomized, controlled investigational device exemption study. Eligible patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The literature reveals that scores above 18.8 are considered a substantial benefit for patients with high levels of disability preoperatively. 31 The specialized literature has suggested the superiority of arthroplasty over intervertebral fusion surgical techniques, 32 data corroborated by our findings. A recent meta-analysis study concluded that after three years of follow-up, the mean percentages for ODI scores were lower among patients who underwent arthroplasty (22.8 points) than patients in the arthrodesis group (27.6 points).…”
Section: Discussionsupporting
confidence: 89%
“…The literature reveals that scores above 18.8 are considered a substantial benefit for patients with high levels of disability preoperatively. 31 The specialized literature has suggested the superiority of arthroplasty over intervertebral fusion surgical techniques, 32 data corroborated by our findings. A recent meta-analysis study concluded that after three years of follow-up, the mean percentages for ODI scores were lower among patients who underwent arthroplasty (22.8 points) than patients in the arthrodesis group (27.6 points).…”
Section: Discussionsupporting
confidence: 89%
“…The final long-term follow-up for Activ-L and Prodisc-L lumbar arthroplasty devices was published in 2021 ( 16 ). This represents the two most rigorously studied LTDR devices.…”
Section: Discussionmentioning
confidence: 99%
“…No patient developed ASD that required surgical intervention. Combined analyses of the FDA trial for ActivL and Prodisc-L demonstrated a reoperation rate of 5.0% at 7 years ( 16 ). We report an index level reoperation rate of 1.7% with M6-L in a 60-year-old male with osteopenia who suffered L4/5 M6-L delayed subsidence and required posterior instrumentation without removal of the LTDR.…”
Section: Discussionmentioning
confidence: 99%
“…The 7-year results of the activL IDE trial were published in 2021. 33 Of note, these results only included activL and ProDisc-L patients. Data were available for 72.7% of patients at 7 years.…”
Section: Activlmentioning
confidence: 99%